![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a; -2\(x\) - 3.(\(x-17\)) = 34 - 2.( - \(x\) + 25)
- 2\(x\) - 3\(x\) + 51 = 34 + 2\(x\) - 50
2\(x\) + 2\(x\) + 3\(x\) = - 34 + 50 + 51
7\(x\) = 67
\(x\) = 67 : 7
\(x\) = \(\dfrac{67}{7}\)
Vậy \(x\) = \(\dfrac{67}{7}\)
b; 17\(x\) + 3.(- 16\(x\) - 37) = 2\(x\) + 43 - 4\(x\)
17\(x\) - 48\(x\) - 111 = 2\(x\) - 4\(x\) + 43
- 31\(x\) - 2\(x\) + 4\(x\) = 111 + 43
- \(x\) x (31 + 2 - 4) = 154
- \(x\) x (33 - 4) = 154
- \(x\) x 29 = 154
- \(x\) = 154 : (-29)
\(x\) = - \(\dfrac{154}{29}\)
Vậy \(x=-\dfrac{154}{29}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có: \(2-\left(15+2x\right)=-5\)
\(\Leftrightarrow2-15-2x+5=0\)
\(\Leftrightarrow-2x-8=0\)
\(\Leftrightarrow-2x=8\)
\(\Leftrightarrow x=-4\)
Vậy: x=-4
b) Ta có: \(\left(x-3\right)^3=-27\)
\(\Leftrightarrow x-3=-3\)
hay x=0
Vậy: x=0
c) Ta có: \(\left(x+1\right)^2=36\)
\(\Leftrightarrow\left[{}\begin{matrix}x+1=6\\x+1=-6\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=5\\x=-7\end{matrix}\right.\)
Vậy: x∈{5;-7}
d) Ta có: \(2x-\left(x+5\right)=1-x\)
\(\Leftrightarrow2x-x-5-1+x=0\)
\(\Leftrightarrow2x-6=0\)
\(\Leftrightarrow2x=6\)
hay x=3
Vậy: x=3
e) Ta có: \(15-\left(-3x+13\right)=2\left(x+1\right)\)
\(\Leftrightarrow15+3x-13-2x-2=0\)
\(\Leftrightarrow x=0\)
Vậy: x=0
![](https://rs.olm.vn/images/avt/0.png?1311)
a)3x-5=-20
3x=-20+5=-15
x=-15:3=-5
b)4-2x^2=-12
2x^2=4--12=16
x^2=16:2=8
x^2 ko bằng
=> ko có số thỏa mãn
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a) 6/2 x+ 1 = 2/7
6/2 x = 2/7 - 1
6/2 x = 2/7 - 7/7
6/2 x = -5/7
x = - 5/7 : 6/2
x = - 5/7 . 2/6
x = -5/21
Ủng hộ nha! :)
BÀI 1 a 6/2x+1=2/7
6/2x=2/7-1
6/2x=-5/7
6*7=5*2x
42=5*2x
42/5=2x
x=42/5:2
x=21/5
![](https://rs.olm.vn/images/avt/0.png?1311)
123-5.(x+4)=38
5(x+4)=123-38
5(x+4)=85
x+4=85:5
x+4=17
x=17-4
x=13
10+2x=2.(32-1)
10+2x=2.(9-1)
10+2x=2.8
2x=16-10
2x=6
x=6:2
x=3
2.x-138=23.32
2.x-138=72
2.x=72+138
2.x=210
x=210:2
x=105
[102+(28-2x)]:20-5=1
(102+28-2x):20=6
130-2x=120
2x=130-120
2x=10
x=10:2
x=5
231-(x-6)=1339:13
231-(x-6)=103
x-6=231-103
x-6=128
x=128+6
x=134
123-5.(x+4)=38
5.(x+4)=123-38
5.(x+4)=85
(x+4)=85/5
x+4=17
x=17-4
x=13
a) \(\frac{5}{13}+2x=\frac{3}{13}\)
\(2x=\frac{3}{13}-\frac{5}{13}=\frac{-2}{13}\)
\(x=\frac{-2}{13}:2=\frac{-2}{13}.\frac{1}{2}=\frac{-1}{13}\)
b) 20% x - 0,7x = 15%
(20% - 0,7)x = 15%
-1/2 x = 15%
x = 15% : (-1/2)
x = -3/10